Neighbourhood care: an experience of activating community care networks in the San Juan / Donibane neighbourhood (Pamplona) - Martínez Virto, Lucía; Hermoso Humbert, Alejandra; Huerta Tardío, Maite (Cuadernos de Relaciones Laborales, 2025)
This article analyses and systematises a process of activation and generation of care networks developed in the San Juan / Donibane neighbourhood of Pamplona /Iruña. Through the development of a qualitative methodology based on the technique of in-depth interviews, we explore the articulation of community action in this neighbourhood around the older care, carrying out a review of its emergence, development and sustainability. The results of the research highlight the potential of the alliance of different agents in the promotion of care networks and their capacity to strengthen care resources in the community. They also underline the importance of factors such as community empowerment, social cohesion and participatory leadership in ensuring the implementation of a strategy based on the participatory action of actors.
Keywords: ageing; community care; neighbourhood; local dimension